PENERAPAN LITERASI KRITIS DALAM PEMBELAJARAN IPS SISWA KELAS VII SMPN 6 KEPULAUAN SELAYAR - Haeruddin; Elpisah, Eka Apriyanti (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article examines the implementation of critical literacy in social science learning subjects for seventh-grade students of SMPN 6 Selayar Island. The method used by the researcher is classroom action research, which was conducted in several stages including planning, action, and reflection. The subjects of the research involved 32 seventh-grade students of SMPN 6 Selayar Island. Data were collected through observation and documentation. Data analysis used data reduction, data presentation, and conclusion. The results showed that the percentage of students’ learning activity achieved a significant improvement in each cycle. In the first cycle, the average value was only 69.06 or 60% classical learning completeness. Yet, after conducting reflection as a step in cycle II, there was an improvement seen from the individual average value, which was 90.31 or 100% classical learning completeness. Thus, the implementation of critical literacy has a significant impact on social science learning subjects for seventh-grade students of SMPN 6 Selayar Island.